2001
DOI: 10.1074/jbc.m008715200
|View full text |Cite
|
Sign up to set email alerts
|

Cdc4p, a Contractile Ring Protein Essential for Cytokinesis inSchizosaccharomyces pombe, Interacts with a Phosphatidylinositol 4-Kinase

Abstract: The proposed function of Cdc4p, an essential contractile ring protein in Schizosaccharomyces pombe, is that of a myosin essential light chain. However, five conditionally lethal cdc4 alleles exhibit complementation in diploids. Such interallelic complementation is not readily explained if the sole function of Cdc4p is that of a myosin essential light chain. Complementation of cdc4 alleles could occur only if different mutant forms can assemble into an active oligomeric complex or if Cdc4p has more than one ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 36 publications
3
55
0
Order By: Relevance
“…Another hypothesis is that cdc4-s16 also compromises the function of some other Cdc4-binding partner that is part of a pathway that normally complements the pathway involving the septins. In this regard, it should be noted that there is good evidence that both S. pombe Cdc4 and its S. cerevisiae counterpart, Mlc1, interact with partners other than the type II myosin heavy chains and that these other partners are also important for cytokinesis (Stevens and Davis 1998;Boyne et al 2000;Shannon and Li 2000;Desautels et al 2001;D'Souza et al 2001;Motegi et al 2001;Win et al 2001;Lord and Pollard 2004;Luo et al 2004;Mulvihill et al 2006;Park et al 2009). The other partners include type V myosin heavy chains (S. pombe Myo51 and perhaps Myo52; S. cerevisiae Myo2), which are thought to be involved in the delivery of new plasma-membrane and cell-wall materials to the division site or (for Myo51) in some unknown function within the AMR; IQGAPs (S. pombe Rng2 and S. cerevisiae Iqg1), which may also be involved in plasma-membrane and cell-wall formation in addition to their roles in AMR function; and a phosphatidylinositol 4-kinase (S. pombe Pik1).…”
Section: Discussionmentioning
confidence: 99%
“…Another hypothesis is that cdc4-s16 also compromises the function of some other Cdc4-binding partner that is part of a pathway that normally complements the pathway involving the septins. In this regard, it should be noted that there is good evidence that both S. pombe Cdc4 and its S. cerevisiae counterpart, Mlc1, interact with partners other than the type II myosin heavy chains and that these other partners are also important for cytokinesis (Stevens and Davis 1998;Boyne et al 2000;Shannon and Li 2000;Desautels et al 2001;D'Souza et al 2001;Motegi et al 2001;Win et al 2001;Lord and Pollard 2004;Luo et al 2004;Mulvihill et al 2006;Park et al 2009). The other partners include type V myosin heavy chains (S. pombe Myo51 and perhaps Myo52; S. cerevisiae Myo2), which are thought to be involved in the delivery of new plasma-membrane and cell-wall materials to the division site or (for Myo51) in some unknown function within the AMR; IQGAPs (S. pombe Rng2 and S. cerevisiae Iqg1), which may also be involved in plasma-membrane and cell-wall formation in addition to their roles in AMR function; and a phosphatidylinositol 4-kinase (S. pombe Pik1).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the ganglioside GM1 and cholesterol were shown to accumulate at the cleavage furrow of dividing Xenopus laevis embryos, where they might regulate Src and PLCγ-dependent signalling (Ng et al, 2005). Recent evidence has also shown that PtdIns(4,5)P 2 accumulates at the cleavage furrow in mammalian and Schizosaccharomyces pombe cells (Desautels et al, 2001;Emoto et al, 2005;Field et al, 2005), whereas phosphatidylinositol (3,4,5)-trisphosphate [PtdIns(3,4,5)P 3 ] is enriched at the poles of the dividing cells (Janetpopoulos et al, 2005) (Fig. 1B).…”
Section: Gangliosides and Phosphoinositides In Cytokinesismentioning
confidence: 99%
“…The furrow then ingresses, leaving a thin intercellular connection between the cells, and a midbody-ring structure is assembled. (B) During furrowing, the composition of the plasma membrane (PM) of the furrow changes -levels of cholesterol, GM1 and PtdIns(4,5)P 2 increase (Desautels et al, 2001;Emoto et al, 2005;Field et al, 2005), PE redistributes into the outer leaflet (Emoto and Umeda, 2000). Increased levels of PtdIns(4,5)P 2 might be controlled by Rab35 (see text).…”
Section: The Role Of Recycling Endosomes During Cytokinesismentioning
confidence: 99%
“…These results demonstrate the evolutionary conservation of the Frq1-Pik1 interaction. Curiously, in Schizosaccharomyces pombe, another small EF-hand-type Ca 2+ -binding protein, Cdc4 (the fission yeast counterpart of S. cerevisiae Mlc1), the ortholog of mammalian myosin light chain (which associates with type V myosins), reportedly interacts physically with the COOH-terminal region of SpPik1 [220]. Because of its role in regulating actin-associated Type V myosin, SpCdc4 was implicated in actin-dependent processes, like cytokinesis [218,219].…”
Section: 22mentioning
confidence: 99%